DEVELOPMENT OF COMPOSITION MODULATION IN CATALYTIC CONVERTERS - Dewi, Arinta
Exhaust emissions, especially nitrogen oxides (NOx), carbon monoxide (CO), sulfur oxides (SOx), volatile organic compounds (VOC), and hydrocarbons (HC), can have negative effects on human health and the surrounding environment. Catalytic converters can be used to control these gas emissions. The purpose of this study is to develop a catalytic converter model in order to obtain optimum conditions with the dynamic mode of composition modulation, and to determine the optimum temperature for both feed and catalyst at steady state mode. The catalytic converter in this study is constructed using a heterogeneous packed-bed reactor (PBR) model. The mathematical model used is a one-dimensional model for multireaction in non-isothermal conditions from a three-way catalytic converter (TWC), where the model equations are derived using mass and energy equilibrium for the fluid and catalyst phases. The modeling and simulation are carried out using FlexPDE 7.18. The model built is validated using the results of the publication of Joshi et al. (2009). The effect of the feed temperature is studied from 350 K to 800 K, while the effect of the catalyst temperature is studied from 300 K to 700 K. Based on the results of the validation the model built is not significantly different from the reference literature, where the feed gas conversion in the literature and this study has a difference in value of less than 10%. The study results show that the conversion efficiency reaches an optimum point at the feed gas or catalyst temperature above the light-off point, which is equal to 502 K. In addition, the higher the catalyst temperature (especially above the light-off), the faster the lightoff time is reached. The dynamic mode that is recommended to increase the average conversion, namely in the operating conditions Tfin ? 500 K, Ts0 300 K, and switching time ? 50 s, with an increase in the average conversion ranging from 4% to 55%. Based on the study results, the proposed mode of operation, in which the average conversion is shown to be higher than the natural start-up mode, is a combination of dynamic and natural start-up modes. At t = 0 to t = 300 s, it is operated in natural start-up mode, then continued in dynamic mode for up to 750 s. The average conversion increases of the proposed modes for CO, H2, HC, and NO are 47.02%, 66.28%, 44.39%, and 53.08%, respectively.